PROSPECTS FOR INVESTING IN FREE ECONOMIC ZONES ON THE TERRITORY OF THE REPUBLIC OF UZBEKISTAN. GLOBAL FLOWS OF FOREIGN DIRECT INVESTMENT (British Journal of Global Ecology and Sustainable Development, 2023)
The state is considering the prospects for investing in a free economic zone (FEZ) on the territory of the Republic of Uzbekistan. The advantages and benefits of this economic model are presented. From the analysis of various types of free economic zones, the main conditions necessary for their creation are determined. The most successful examples of the application of this idea in Uzbekistan are given. Analysis and analysis of the basic principles of doing business and investment projects on the territory of the free economic zone. Also, the state is considering a document on world investment for 2022.